SECOND LANGUAGE ANXIETY AND ACHIEVEMENT: A META-ANALYSIS - Teimouri, Yasser; Goetze, Julia; Plonsky, Luke (Studies in second language acquisition, 2019)
Second language (L2) anxiety has been the object of constant empirical and theoretical attention for several decades. As a matter of both theoretical and practical interest, much of the research in this domain has examined the relationship between anxiety and L2 achievement. The present study meta-analyzes this body of research. Following a comprehensive search, a sample of 97 reports were identified, contributing a total of 105 independent samples (N = 19,933) from 23 countries. In the aggregate, the 216 effect sizes (i.e., correlations) reported in the primary studies yielded a mean of r = −.36 for the relationship between L2 anxiety and language achievement. Moderator analyses revealed effects sizes to vary across different types of language achievement measures, educational levels, target languages, and anxiety types. Overall, this study provides firm evidence for both the negative role of L2 anxiety in L2 learning and the moderating effects of a number of (non)linguistic variables. We discuss the findings in the context of theoretical and practical concerns, and we provide direction for future research.